2020
DOI: 10.22230/cjc.2020v45n2a3541
|View full text |Cite
|
Sign up to set email alerts
|

Examining How Newcomer Women to Canada Use Social Media for Social Support

Abstract: Background This study utilized an exploratory sequential mixed-method research design to examine how newcomer women in Canada use social media for support to enhance their mental well-being.Analysis The qualitative findings revealed that social media helped these newcomer women both before and after their arrival in Canada. The quantitative results showed that newcomer women mostly use social media for receiving information, followed by esteem support, networking, and emotional support.Conclusion and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…We found only one study that explored the use of social media for newcomer women [39]. There was a significant positive association reported between the use of Facebook and Twitter platforms for emotional support.…”
Section: Social Media Interventionmentioning
confidence: 85%
See 3 more Smart Citations
“…We found only one study that explored the use of social media for newcomer women [39]. There was a significant positive association reported between the use of Facebook and Twitter platforms for emotional support.…”
Section: Social Media Interventionmentioning
confidence: 85%
“…Of the fourteen studies included in this review, the types of studies varied considerably, representing a diverse range of research methodologies. These included pilot studies [36,37], an exploratory sequential mixed-methods study [39], a scoping review [33], a case report [40], qualitative studies [29][30][31][32]34,36], a literature review [28], a case series [38], and a systematic review [35]. When considering the sample sizes of the studies, it was observed that 2 studies had fewer than 9 participants [36,40], 3 studies had a sample size ranging from 10 to 29 participants [30,31,39], and 4 studies had a larger sample size of more than 30 participants [17,29,34,37].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“… 2. Although there is evidence from, for example, Canada that non-Western migrants likewise draw on social media for such support (Zaher, 2020). …”
mentioning
confidence: 99%